Effect of coal waste powder in hot mix asphalt compared to conventional fillers: mix mechanical properties and environmental impacts. (15th March 2015) - Modarres, Amir; Rahmanzadeh, Morteza; Ayar, Pooyan
Abstract: The demand for using waste has significantly increased because of the depletion and limitation of the natural resources. Coal waste is a by-product that produced in coal washing plants. The accumulation of coal waste in the nature causes several ecological and environmental problems. The main objective of this study was to investigate the applicability of coal waste powder and its produced ash as fillers in hot mix asphalt (HMA) compared to the conventional fillers. In this study, other conventional fillers including limestone powder, zeolite powder and ordinary Portland cement were also used. Experimental tests have been performed to evaluate the mechanical properties of HMA containing different fillers. Accordingly, Marshall stability, indirect tensile strength, moisture sensitivity, resilient modulus and fatigue tests were conducted. Environmental impact of using coal waste filler in HMA was evaluated by using toxicity characteristic leaching procedure (TCLP). The results of the mechanical tests indicated that the use of coal waste powder and especially its ash improved the performance of HMA compared to limestone and zeolite. Furthermore, the use of the coal waste ash resulted in nearly similar mechanical properties to ordinary Portland cement. The heavy metal leachates in TCLP test showed to a large extent similar results for different studied samples which all were below the regulation levels. Finally, it can be concluded that, the use of coal waste powder as filler in HMA not only leads to desired mechanical properties, but also reduces the volume of the pollutants waste in environment. Highlights: The mechanical and environmental impacts of using coal waste in HMA were investigated. Effect of coal waste powder and its ash compared to limestone, zeolite and cement. The use of coal waste and its ash improved the stiffness and fatigue behavior of HMA. Between compared fillers only cement had to some extent better impacts than the coal waste. Heavy metals concentration in HMA containing coal waste was similar to other fillers.